RANCANG BANGUN SISTEM INFORMASI PENGINGAT JADWAL DINAS DOKTER PADA RUMAH SAKIT KELUARGA SEHAT PATI BERBASIS SMS GATEWAY (Information Technology and Telematics, 2013)
SMS (Short Message Service) has been used by humans. Besides having a wide range, to reach rural areas, easy to use and efficient SMS, SMS Gateway is a two-way communication using the normal rates in accordance with the rates applied by the operator. SMS Gateway has a variety of types.  Information systems reminder SMS based doctor services are designed to be applied to the Keluarga Sehat Pati Hospital. In this application, the authors utilize SMS Gateway application with two features, namely SMS Reminder (Reminder) and SMS Autorespond. With the SMS Reminders, is expected to help doctor in reminding his official schedule, while via SMS Autorespond doctor can check the schedule as a whole. The programming language used in designing the SMS application is PHP. For data storage, the authors use MySQL. As for building SMS applications, the author uses Gammu. This application, can alert clinicians based schedule SMS reminders twice, namely on the day, exactly one hour before the doctor's office and on H-1 or one day prior to the doctor's office, which is at 19:00 pm. Keywords — SMS (Short Message Service), Gammu, SMS Gateway, SMS Reminder, SMS Autorespond.